'British Small Craft': the cultural geographies of mid-twentieth century technology and display - Fenner, James Lyon (2014)
The British Small Craft display, installed in 1963 as part of the Science Museum’s new Sailing Ships Gallery, comprised of a sequence of twenty showcases containing models of British boats—including fishing boats such as luggers, coracles, and cobles—arranged primarily by geographical region. The brainchild of the Keeper William Thomas O’Dea, the nautical themed gallery was complete with an ocean liner deck and bridge mezzanine central display area. It contained marine engines and navigational equipment in addition to the numerous varieties of international historical ship and boat models. Many of the British Small Craft displays included accessory models and landscape settings, with human figures and painted backdrops.